Residual Toxicity of Abamectin, Chlorpyrifos, Cyromazine, Indoxacarb and Spinosad on Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) in Greenhouse Conditions - Askari Saryazdi, Ghasem; Hejazi, Mir Jalil; Saber, Moosa (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Liriomyza trifolii is an important pest of vegetable crops in many parts of the world including Iran. In this study potted bean plants were sprayed with recommended field rates of abamectin, chlorpyrifos, cyromazine, indoxacarb and spinosad. To assess the residual activities of these insecticides, the plants were infested with L. trifolii adults 2 hours; 1, 3, 5, 7, 10, 15, 20, 25 and 35 days after insecticidal treatments. The adults were allowed to stay on treated plants for eight hours. The treated plants were kept in a greenhouse. Number of feeding stipples and larval mines on leaves, as well as pupation and adult eclosion rates were assessed. Two-way ANOVA procedure of SAS was used for statistical analysis and the treatment means were separated using Duncan’s multiple range test. Abamectin and spinosad severely affected egg hatching and embryonic development. Eggs oviposited in leaves with residues of chlorpyrifos up to 5 days old, had reduced hatching. Larval development was also, affected by residues of chlorpyrifos up to four weeks old. Indoxacarb reduced larval development and adult eclosion in treatments with up to 20 days old residues. Cyromazine had no effect on the number of larval mines, but, pupation was severely hampered and adult eclosion was completely ceased even in treatments with five weeks old residues. Determining the residual activity of insecticides used for controlling this pest is useful in avoiding unnecessary treatments.